Implementation of the Contextual Teaching and Learning (CTL) Learning Model Assisted by Audio Visual Media in Science Learning for Grade IV Students - Cahyani, Devi; Sofiarini, Andriana; Abadi, Candres (Global Education Journal, 2025)
Learning is a process of conveying thoughts that occurs between educators and students. This study aims to determine the completeness of the science learning outcomes of fourth-grade students of SD Negeri 1 Tugu Sempurna after the application of the Contextual Teaching and Learning learning model assisted by Audio Visual media. This research method uses a quantitative approach with experiments. The research design used in this study is a pre-experimental design with one group pre-test and post-test categories. The subjects of this study were 25 fourth-grade students of SD Negeri 1 Tugu Sempurna consisting of 9 boys and 16 girls. Data collection techniques were carried out by observation, interviews, tests to students and documentation. The results of the study showed that there was completeness of student learning outcomes after the application of the Contextual Teaching and Learning learning model assisted by Audio Visual media. Based on the data analysis that has been done, the average pre-test test score is 51.60 and the average post-test test score is 78.76 after the application of the Contextual Teaching and Learning learning model assisted by Audio Visual media. Based on the z-test analysis, the z-count value ≥ z-table, which is 4.829 ≥ 1.65, is obtained. This means that Ho is rejected and Ha is accepted, so it can be concluded that the learning outcomes of fourth-grade students of SD Negeri 1 Tugu Sempurna are complete after the implementation of the Contextual Teaching and Learning learning model assisted by Audio Visual Media.